Diffuser Optimation at Exhaust System with Catalytic Converter for 110 cc Mopet with Fluid Flow CFD Simulation - Soemardi, Tresna P.; Siswantara, Ahmad Indra; Erwin, Erwin (UI Scholars Hub, 2003)
Diffuser Optimation at Exhaust System with Catalytic Converter for 110 cc Mopet with Fluid Flow CFD Simulation. CFD simulation used to get behavior of exhaust gas through catalyst, this result will be used to optimize geometry form to perform uniform stream distribution to catalyst, and CFD Simulation will used to analyze backpressure that happened at the model.